Meningkatkan Sikap Kerjasama Siswa Kelas V Melalui Penerapan Model Problem Based Learning pada Mata Pelajaran Pendidikan Pancasila - Izzah Millati; Agustina Tyas Asri Hardini (Jurnal Profesi Pendidikan, 2025)
This class action research aims to improve the cooperation attitude of fifth-grade students through the application of the problem-based learning (PBL) model in Pancasila education subjects. This research employs a class action approach and utilizes both qualitative and quantitative methods. The design of this study provides two cycles, and each cycle consists of several stages, namely planning, observation or action, and reflection. The results of this study indicate that (1) before implementing the problem-based learning (PBL) model in Pancasila education, the cooperation attitude of fifth-grade students at SDN Mangunsari 02 was measured at 51%, which falls under the “less” criteria. (2) After cycle I, grade V students at SDN Mangunsari 02 showed an increased cooperation attitude in learning Pancasila education, reaching a percentage of 73% with “sufficient” criteria. (3) After the second cycle, fifth-grade students at SDN Mangunsari 02 showed an increased cooperation attitude in learning Pancasila education, reaching 86% with the criteria “Good.” So that the class assessment was stopped in cycle II because it had reached the success indicator with a minimum percentage of 80% with “Good” criteria. It can be seen that there is a significant increase between the percentage value before action and after action, and it can be concluded that the problem-based learning (PBL) learning model can increase the attitude of cooperation in pan education subjects.